2006
DOI: 10.1136/bmj.38959.650903.7c
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of academic performance of twins and singletons in adolescence: follow-up study

Abstract: Objectives To determine whether twins in recent cohorts show similar academic performance in adolescence to singletons and to test the effect of birth weight on academic performance in twins and singletons. Design Follow-up study. Setting Denmark. Participants All twins (n = 3411) and a 5% random sample of singletons (n = 7796) born in Denmark during 1986-8. Main outcome measures Test scores in ninth grade (age 15 or 16), birth weight, gestational age at birth, parents' age, and parents' education. Results Nin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

19
96
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 129 publications
(117 citation statements)
references
References 18 publications
19
96
1
1
Order By: Relevance
“…This might limit extrapolation of results of twin studies. However, twins do not appear to differ markedly from singletons for most types of characteristics [10,31]. In addition, the prevalence of weekly LBP in this 11-year-old twin population (6.6%) is very similar to that found in a representative sample of Finnish schoolchildren aged 10-12 (6.4%) [27].…”
Section: Discussionsupporting
confidence: 69%
“…This might limit extrapolation of results of twin studies. However, twins do not appear to differ markedly from singletons for most types of characteristics [10,31]. In addition, the prevalence of weekly LBP in this 11-year-old twin population (6.6%) is very similar to that found in a representative sample of Finnish schoolchildren aged 10-12 (6.4%) [27].…”
Section: Discussionsupporting
confidence: 69%
“…This finding is contrary to results from recent twin studies showing that adolescent and adult twins do not score below nontwins on general intelligence tests (2,3).…”
contrasting
confidence: 56%
“…[1][2][3][4][5] We showed in a twin study that part of the positive association between birth weight and childhood IQ may be mediated by genetic effects. 2 We are interested whether there is any relation between catch-up growth and cognition, because a recent study reported that in zebra finches the level of compensatory growth after a period of poor nutrition was associated with long-term negative consequences for cognitive function.…”
mentioning
confidence: 99%